THE EFFECT OF AUDIT COMPETENCE, SKEPTISISM, SELF ESTEEM, ROLE COMPLICATIONS, RELIGIOSITY TO AUDIT QUALITY - Hotbin Hasugian (International Journal of Contemporary Accounting, 2022)
AbstractThis study examines audit quality as a dependent variable and auditor competence, skepticism, self esteem, role complication and religiosity as independent variables. This study aims to analyze the influence of independent variables to the dependentent variable in this study. The test was conducted on 125 auditor respondents who have been certified or not yet certified in North Sumatra provincial government environment and the data is complete and can be analyzed. Variable testing techniques using multiple linear regression techniques.               The results showed that auditor competence, skepticism, role conflict and religiosity have a significant effect on audit quality, while self esteem does not affect audit quality. The results of the study are expected to contribute empirically that auditor competence, skepticism, role complicity and religiosity determine the quality of audit and the results of this study are also expected to provide input to the local government the importance of increasing the value of competence, the maximum role and most importantly good spiritual qualities must be excavated by giving training and education.